Effect of Active Teaching and Learning on Students’ Reading Skills in Selected Secondary Schools of Sheema Municipality. - Atuheire, Janis (Kabale University, 2025)
The study examined the impact of active teaching and learning on students' reading skills in selected secondary schools within Sheema Municipality. The objectives included examining the influence of active teaching and learning in these schools, identifying the types of reading skills used by students, and investigating teaching methods and their impact on students' English language reading skills. A cross-sectional study design was employed, and data were collected through interviews and questionnaires. Findings on the influence of active teaching and learning showed that the majority of respondents believed it helps teachers guide students during class discussions, while fewer respondents indicated that it encourages students to develop a participatory mindset. Regarding the types of reading skills, most respondents reported using intensive reading, while scanning was the least mentioned skill. In terms of teaching methods, the most commonly mentioned approach was the use of discussions, while role-play and the discovery method were less frequently cited. The study recommended that school administrators develop policy guidelines for assessing reading comprehension to improve performance in both public and private schools.